Swadesh

1(0!) + 3(1!) + 7(2!) + 13(3!) + 21(4!) + 31(5!) ...... n terms = 2015(2015!)

find the value of n.

2015 4030 8060

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Maggie Miller
Aug 2, 2015

The terms in this series are ( k ( k 1 ) + 1 ) ( ( k 1 ) ! ) (k(k-1)+1)((k-1)!) . Note 1 ( 0 ! ) = 1 ( 1 ! ) 1(0!)=1(1!) and 1 ( 0 ! ) + 3 ( 1 ! ) = 2 ( 2 ! ) 1(0!)+3(1!)=2(2!) .

Suppose the sum of the first m m terms is m ( m ! ) m(m!) . Then the sum of the first m + 1 m+1 terms is

m ( m ! ) + ( m ( m + 1 ) + 1 ) ( m ! ) = ( m 2 + 2 m + 1 ) ( m ! ) m(m!)+(m(m+1)+1)(m!)=(m^2+2m+1)(m!)

= ( m + 1 ) 2 ( m ! ) = ( m + 1 ) ( ( m + 1 ) ! ) =(m+1)^2(m!)=(m+1)((m+1)!) .

Then inductively, the sum of the first m m terms is m ( m ! ) m(m!) for any natural numbers m m .

In particular, the sum of the first 2015 \boxed{2015} terms is 2015 ( 2015 ! ) 2015(2015!) .

Swadesh Rath
Aug 2, 2015

see basically we can resolve the coefficients as - n^2 - n + 1 so rth term = (r-1)! * ( r^2 - r + 1 )

so open the brackets - t rth term r * r ! - r! + (r-1)! so, hence if u add terms t1 , t2 , t3 ... consecutive terms are cancelled ... left terms = 1 1! + 2 2! +3 3! ... n n! + 0! - n! but 1 * 1 ! + 2 * 2 ! ... n * n! = (n+1)! +1 ... so final results comes out to be ... n(n!) ... so answer is 2015

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...